1989
DOI: 10.1111/j.1365-2141.1989.tb07731.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary stomatocytosis: consistent association with an integral membrane protein deficiency

Abstract: We studied the RBC membrane proteins of four patients, including a mother and daughter, with hereditary stomatocytosis. One- and two-dimensional gel electrophoresis revealed that a 28 kDa integral protein, present in normal RBC membranes, was absent in all four patients. This abnormality, reported once previously (Lande et al, 1982), appears to be a characteristic feature of hereditary stomatocytosis, and may be related to the underlying permeability defect in this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However, this topography has not been directly demonstrated. Importantly, mutations leading to the absence of stomatin result in osmotically fragile cells with increased cation fluxes and elevated intracellular sodium concentrations [6568]. Moreover, observations that Milan hypertensive rats, which carry a mutation in both β and α adducin genes, also display increased erythrocyte cation fluxes [69] have suggested that regulation of cation transport may depend on an interaction between adducin and stomatin.…”
Section: Protein Interactions Of Erythrocyte Adducinmentioning
confidence: 99%
“…However, this topography has not been directly demonstrated. Importantly, mutations leading to the absence of stomatin result in osmotically fragile cells with increased cation fluxes and elevated intracellular sodium concentrations [6568]. Moreover, observations that Milan hypertensive rats, which carry a mutation in both β and α adducin genes, also display increased erythrocyte cation fluxes [69] have suggested that regulation of cation transport may depend on an interaction between adducin and stomatin.…”
Section: Protein Interactions Of Erythrocyte Adducinmentioning
confidence: 99%
“…This leak can be "plugged" by treatment of the cells with the cross-linker dimethyl adipimate (327), strongly suggesting that a transmembrane protein channel is responsible for this leak. Hereditary stomatocytosis patients have no detectable levels of the stomatin protein in their red cells (129,263). Thus, the absence of stomatin appears to correlate with a transmembrane cation link, suggesting the stomatin is a regulator of some ion channel.…”
Section: Stomatinmentioning
confidence: 99%
“…Attention was drawn to the protein by its absence from the red cell membrane in the dominantly-inherited haemolytic anaemia, hereditary stomatocytosis, in which the red cells show a catastrophic leak to the univalent cations Na+ and K+ (Lock et al 1961;Lande et al 1982;Eber et al 1989;Stewart and Turner 1999;Stewart and Fricke 2003). However, the stomatin gene is not mutated in this condition, and this anaemia does not represent the phenotype of a human stomatin 'knock out' (Wang et al 1992.…”
Section: Introductionmentioning
confidence: 98%